GRANIT NGUỒN GỐC VỎ KHỐI TAM TAO: CƠ SỞ CỦA TUỔI PERMI MUỘN - Anh, Phan Lưu; Hằng, Hoàng Việt (Vietnam Journal of Earth Sciences, 2017)
Crustal-derived Tam Tao granite formed a small intrusive, which has a simple composition, mainly of granite biotite. From poin of view of petrochemical composition: SiO2 (62,68-68,60 %), Na2O (2,46-2,85 %), Al2O3 (13,78-15,06 %), ACNK = 1,0-1,4 and mineralogical composition (biotite±muscovite±garnet±cordierite) this granite is metaluminous and belongs to S-granite type [1]. According to rareelements, Tam Tao granite could be considered asa classic palingen S-granite. Comparing withpalingen granite of alkaline-calcarius type, this granite complex is characterized by low content of Sr and Ba, high content of lithophile elements.Tam Tao granite has an assimetry spectrum REE with (Ce/Yb)N ratio about 100-120. The content oflight lantanoid higher 50-200 time than chondrite,while content heavy lantanoid is higher only 10-40 time and has minimum Eu (t.Eu = 0,46-0 ,52). Absolute dating by isotopic Ar-Ar on biotite shows: T = 250,5 ±1 Ma. Nd-Sm dating shows :  εNd(t) = -10,1, the ratio 147Sm/144Nd has 0,141146, TNd(CHUR) =1,2 Ga. Combining these absolute datings canmake conclusion that the age of Tam Tao granite is 250,5 Ma (corresponds P2). This granite belongs tospecific S-granite, formed from stable continentalcrust, that is no younger than 1,2 Ga.